Does capital market opening promote enterprise green innovation? Evidence from Shanghai-Hong Kong stock connect and Shenzhen-Hong Kong stock connect - Lyu, Yanwei; Wang, Zuo; Zhang, Jinning (Technological and Economic Development of Economy, 2023)
This study selects Chinese A-share listed enterprises from 2010 to 2020 as the research sample, constructs a Difference-in-differences model to analyze the Shanghai-Hong Kong stock connect and Shenzhen-Hong Kong stock connect policy on enterprise green innovation. The transmission channels are tested, and the heterogeneity of this impact is further explored. It is found that the Shanghai-Hong Kong stock connect and Shenzhen-Hong Kong stock connect policy has significantly improved the total level, quality and quantity of enterprise green innovation, and the effect on the total level and quality is greater than the quantity. The Shanghai-Hong Kong stock connect and Shenzhen-Hong Kong stock connect policy can effectively alleviate the financing constraints faced by enterprises, improve the information environment of enterprises, and thus improve their green innovation. There is heterogeneity in the nature of property rights, corporate social responsibility, industry monopoly and regional marketization in the promotion of enterprise green innovation by the Shanghai-Hong Kong stock connect and Shenzhen-Hong Kong stock connect policy.First published online 21 July 2023